Development of Computational Model of Motorcycle and Rider During Collision - Arwardy, Aziz Fathurrahman; Mohamad, Zaleha (Journal of Sustainable Manufacturing in Transportation, 2022)
The goal of this project is to develop the computational model of motorcycle and rider for deformable body. Also, to identify the response of rider and motorcycle on collision.  Computational model is the one method that can replace the actual experiment on crash test. From the simulation can save cost by actual impact crash test. This project begins with design the model of actual motorcycle. Because the model of the project using Honda Wave 100R is to complex and the computer not powerful enough to generate mesh the simplified model is use for the project. Then, the material of this project using ANSI 304 stainless steel. The simulation of the experiment run by the ANSYS software to calculate mathematical model result after impact. Finally, the result of deformation was recorded to compare the result of deformation on actual crash test. The Comparison result of deformation actual and simulation are quietly similar